Educational Streaming, Occupational Choice, and the Distribution of Wages - Kelly Bedard (Luxembourg Income Study (LIS), 1997)
This paper studies how the structure and quality of education influence occupational choices and the distribution of wages. Structure refers to the age at which children are streamed into specialized programs as well as the proportion of students placed in each stream. The Roy (1951) model of occupational choice is extended to incorporate the streaming of students into different programs based on academic ability prior to the point at which they self-select into an occupation. Streaming dates and the relative size of each stream have important implications for sectoral selection and the distribution of wages.
Keywords: 330; Einkommensverteilung; Berufsbildung; Berufsbildungspolitik; Theorie; Deutschland